SAMBAS INTERNATIONAL ISLAMIC CENTER - Gebi Gebi; Irwin Irwin; Lestari Lestari (JMARS: Jurnal Mosaik Arsitektur, 2022)
Islam developed rapidly in Sambas Regency during the era of the Sambas Sultanate of Sultan Muhammad Syafiuddin II (1688-1922) and was nicknamed "The Veranda of Mecca". The strategic position of Sambas Regency on the border with Malaysia and Brunei Darussalam and close to Southeast Asian countries has the opportunity to establish an international standard forum. One of these forums is in the form of an Islamic Center carrying an international standard to continue to foster the spirit and Islamic values based on the Qur'an and As-Sunnah in Sambas Regency in this modern era. The Islamic Center is a forum that accommodates various activities of fostering and developing muslim communities based on Islamic teachings such as worship, muamalah, science, da'wah, information centers, and Islamic symbols, as well as community empowerment centered in one area. The method used in this design is the five-step method by McGinty (1979) which includes initiation, preparation, proposal submission, evaluation, and action. This design consists of the main, supporting, and supporting functions. The main functions are worship, islamic information center, islamic religious education, social, commercial, and services. Support functions include sports and lodging and support functions include management and service functions. The result of this design is the formation of a Sambas International Islamic Center area with multi-mass buildings including mosques, self-service commercial buildings, workshops and islamic banks, library and social buildings, multi-purpose buildings, male and female education buildings, management buildings, sports buildings, and a male and female dormitory building.